Strengthening fairness, transparency and accountability in health care priority setting at district level in Tanzania - Stephen Maluka (Taylor & Francis Group, 2011)
Health care systems are faced with the challenge of resource scarcity and have insufficient resources to respond to all health problems and target groups simultaneously. Hence, priority setting is an inevitable aspect of every health system. However, priority setting is complex and difficult because the process is frequently influenced by political, institutional and managerial factors that are not considered by conventional priority-setting tools. In a five-year EU-supported project, which started in 2006, ways of strengthening fairness and accountability in priority setting in district health management were studied. This review is based on a PhD thesis that aimed to analyse health care organisation and management systems, and explore the potential and challenges of implementing Accountability for Reasonableness (A4R) approach to priority setting in Tanzania. A qualitative case study in Mbarali district formed the basis of exploring the sociopolitical and institutional contexts within which health care decision making takes place. The study also explores how the A4R intervention was shaped, enabled and constrained by the contexts. Key informant interviews were conducted. Relevant documents were also gathered and group priority-setting processes in the district were observed. The study revealed that, despite the obvious national rhetoric on decentralisation, actual practice in the district involved little community participation. The assumption that devolution to local government promotes transparency, accountability and community participation, is far from reality. The study also found that while the A4R approach was perceived to be helpful in strengthening transparency, accountability and stakeholder engagement, integrating the innovation into the district health system was challenging. This study underscores the idea that greater involvement and accountability among local actors may increase the legitimacy and fairness of priority-setting decisions. A broader and more detailed analysis of health system elements, and socio-cultural context is imperative in fostering sustainability. Additionally, the study stresses the need to deal with power asymmetries among various actors in priority-setting contexts.